Laboratory safety evaluation at the Ethiopian Public Health Institute, 2018-2019 - Stephanie Ringler; Emily G. Pieracci; Sylvia Murphy; Asefa Deressa; Fatuma Yassin Bushra; Theresa Kanter; Getnet Yimer; Lillian A. Orciari; Mary Reynolds; Lauren Greenberg (Journal of Global Health Reports)
# Background In 2015, Ethiopia designated rabies as a priority zoonotic disease. Challenges in rabies diagnostic capacity, including laboratory safety, were identified in 2016. As a pilot evaluation, the national rabies laboratory in Ethiopia (EPHI) was chosen to participate in an evaluation of necropsy laboratory facilities and procedures which was conducted over two years. This evaluation identified areas for improvement that strengthening would enhance safety in the laboratory environment. Process changes, specifically in cleaning procedures, will decrease the likelihood of cross contamination and improve precision of testing.